Characterization of the Aerobic Anoxygenic Phototrophic Bacterium Sphingomonas sp. AAP5 - Kopejtka, Karel; Zeng, Yonghui; Kaftan, David; Selyanin, Vadim; Gardian, Zdenko; Tomasch, Jürgen; Sommaruga, Ruben; Koblížek, Michal (Microorganisms, 2021)
An aerobic, yellow-pigmented, bacteriochlorophyll a-producing strain, designated AAP5 (=DSM 111157=CCUG 74776), was isolated from the alpine lake Gossenköllesee located in the Tyrolean Alps, Austria. Here, we report its description and polyphasic characterization. Phylogenetic analysis of the 16S rRNA gene showed that strain AAP5 belongs to the bacterial genus Sphingomonas and has the highest pairwise 16S rRNA gene sequence similarity with Sphingomonas glacialis (98.3%), Sphingomonas psychrolutea (96.8%), and Sphingomonas melonis (96.5%). Its genomic DNA G + C content is 65.9%. Further, in silico DNA-DNA hybridization and calculation of the average nucleotide identity speaks for the close phylogenetic relationship of AAP5 and Sphingomonas glacialis. The high percentage (76.2%) of shared orthologous gene clusters between strain AAP5 and Sphingomonas paucimobilis NCTC 11030T, the type species of the genus, supports the classification of the two strains into the same genus. Strain AAP5 was found to contain C18:1ω7c (64.6%) as a predominant fatty acid (>10%) and the polar lipid profile contained phosphatidylglycerol, diphosphatidylglycerol, phosphatidylethanolamine, sphingoglycolipid, six unidentified glycolipids, one unidentified phospholipid, and two unidentified lipids. The main respiratory quinone was ubiquinone-10. Strain AAP5 is a facultative photoheterotroph containing type-2 photosynthetic reaction centers and, in addition, contains a xathorhodopsin gene. No CO2-fixation pathways were found.
Keywords: aerobic anoxygenic phototrophic bacteria; rhodopsin; photosynthesis genes; bacteriochlorophyll a; Sphingomonadaceae